Power, Gerald & Pilný, Ondřej. Ireland and the Czech Lands: Contacts and Comparisons in History and Culture. - Bolfarine, Mariana (ABEI Journal, 2014)
Power, Gerald & Pilný, Ondřej. Ireland and the Czech Lands: Contacts and Comparisons in History and Culture. Bern: Peter Lang, 2014. 235 pp.